ENHANCING ENGLISH PROFICIENCY THROUGH IMMERSIVE LEARNING - Aini, Qurrotul; Asan, Nassuha (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2025)
The International Community Service Program (KKN) at Darul Furqon School in Narathiwat, Thailand, aimed to enhance the English language skills of senior high school students through two main activities: teaching English at school and conducting an "English Day" program at the student dormitory. Observations revealed significant challenges in student English proficiency, including limited vocabulary, poor pronunciation, and low grammar skills, compounded by a lack of motivation and teachers' reliance on Thai in the classroom. The KKN program utilized a communication-focused approach, emphasizing vocabulary building, pronunciation practice, and grammar through interactive and immersive activities. The results showed measurable improvements in student confidence and English language use, with students demonstrating better vocabulary implementation, increased speaking confidence, and enhanced understanding of grammar. The program also fostered a collaborative learning environment, benefiting both students and teachers, and offered an innovative model that could be adopted in similar educational settings to improve English language proficiency.